Sustainable Waste Management Through Takakura Composting Socialization For The Community of Centong Village, Mojokerto - Francesca Almi Financia; R. Azizah; Brigade Mahendra Dharmalaksana; Adinda Febry Maghfiroh; Gysella Julia Nurmalasari (Interdisciplinary Social Studies, 2026)
The management of household organic waste remains a significant challenge in various rural areas of Indonesia, including Centong Village, Gondang Subdistrict, Mojokerto Regency. The SIKOMPAS program (Socialization of Takakura Composting for the Community) was implemented as a community service initiative by the BBK student team of Universitas Airlangga to introduce organic waste management methods using the Takakura composting technique and the utilization of Black Soldier Fly (BSF) larvae. The program employed an educative and participatory approach through hands-on demonstrations and knowledge evaluation via pre- and post-tests. The results showed a significant increase in participants’ understanding of key concepts, technical steps, and the environmental and economic benefits of the Takakura and BSF composting methods. All participants demonstrated active involvement and improved post-test scores across nearly all knowledge indicators. The program also contributed to achieving SDG 3 (Good Health and Well-being), SDG 11 (Sustainable Cities and Communities), and SDG 13 (Climate Action) through reduced air pollution from waste burning and mitigation of greenhouse gas emissions. Thus, SIKOMPAS is effective as a community-based intervention in establishing an independent, low-emission, and sustainable organic waste management system.